Quantifying electronic band interactions in van der Waals materials using angle-resolved reflected-electron spectroscopy - Johannes Jobst (Nature Portfolio, 2016)
Heterostructures of graphene and hexagonal boron nitride have great potential for high-mobility electronics, yet little is known about the electronic interaction between these two atomically thin materials. Here, the authors perform angle-resolved reflected-electron spectroscopy to unveil their interplay.